Berbagai Tanaman Rempah Sebagai Sumber Antioksidan Alami - Ayu Nirmala Sari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
Radicals produced naturally in the body, can cause various diseases when present in large quantities. High levels of free radical compounds showed low antioxidant activity that leads to degeneration of the body cells, metabolic disorder, decreased immune response that trigger the emergence of a variety of degenerative diseases. Need extra antioxidants from outside the body in order to help prevent the adverse effects of free radicals, such as antioxidants derived from plants used as cooking ingredients or food ingredients. There are some herbal plants that are a source of natural antioxidants , which are also used as a spice, such as turmeric (Curcuma domestica), ginger (Zingiber offcinale), nutmeg (Myristica fragrans), paprika (Capsicum annum), lemongrass (Cymbopogon citratus), galangal (Alpinia galangal), onion (Allium cepa) and garlic (Allium sativum).